Isolation and Proteomic Analysis of Platelets by SELDI-TOF MS - Downing, Sean R. (Methods Mol Biol, 2012)
Many growth factors, leukotrines, and biological ligands are not circulating free in plasma or serum, except in the case of late or disseminated disease. During early tumor growth and angiogenesis, platelets actively and selectively sequester regulators of angiogenesis and, as such, the platelet protein content can be used as a marker of early tumor growth or angiogenesis. With the recent increase in the clinical use of biologic modifiers in cancer and chronic disease therapy, the search for markers of early disease, therapeutic response, and/or recurrence has suggested that analysis of platelet proteins may be more relevant and accurate. We provide a guideline for the proteomic analysis of platelet proteome, placing specific emphasis on angiogenesis regulators, even though other platelet proteins may serve as markers of disease in the future. The analysis of serum/plasma has been fraught with difficulties because of the extraordinarily large number of proteins and because some of the proteins are contained in extraordinarily large amounts, masking the less abundant proteins. Thus, platelets may provide a much more biologically relevant analyte for biomarker discovery.